Analisis Ketahanan Pangan dan Karakteristik Rumah Tangga dengan Kejadian Stunting - Nathasa Weisdania Sihite; Yunita Nazarena; Firda Ariska; Terati Terati (Jurnal Kesehatan Manarang, 2021)
Stunting is a condition of chronic growth failure experienced by toddlers that can cause children to experience difficulties in achieving optimal growth and development according to their age. Stunting can be minimized if the factors that affect stunting in the region can be controlled properly. Many factors are thought to influence the incidence of stunting, one of which is food security. If food insecurity occurs in a household, this can increase the proportion of stunting events that are increasing which can directly increase the national stunting incidence rate and will continue to be a major health problem in Indonesia. Indonesia. The purpose of this study was to analyze the relationship between household food security and household social factors with the incidence of stunting. The research was conducted in Palembang City, precisely at the 11 Ilir Health Center in Palembang. The research method used is a cross-sectional design. The determination of the research sample was carried out by purposive sampling based on the inclusion and exclusion criteria of the sample that had been determined in this study. The research sample was toddlers aged 0 – 59 months totaling 40 people. Analysis of the data used is chi-square with = 0.05. In this study, it was found that there was a significant relationship between household food security (p = 0.031), and household size (p = 0.000) with the incidence of stunting, while for the variable mother's age (p = 0.393) and mother's education level (p = 0.283) is known to have no significant relationship with the incidence of stunting. Household food security is directly related to the incidence of stunting, families in households who are not food insecure tend to have children under five who are classified as stunting, this is due to the lack of nutritional intake received both in terms of quantity and quality and does not meet the nutritional adequacy standard for stunting toddlers. It is hoped that to reduce the incidence of stunting, the government needs to add a local food-based work program in reducing the incidence of stunting.